Electrochemical Investigation of Metal Oxide Conducting Electrodes for Direct Detection of Sulfide. Issue 5 (12th March 2015) - Aziz, Md. Abdul; Sohail, Manzar; Oyama, Munetaka; Mahfoz, Wael
Abstract This study examined the performance of four conducting metal oxide electrodes for the direct electrochemical analysis of sulfide; the electrode materials studied were indium tin oxide (ITO), fluorine doped tin oxide (FTO), aluminum doped zinc oxide (AZO) and gallium doped zinc oxide (GZO). Cyclic voltammetry (CV) results obtained using the ITO, AZO, GZO and FTO electrodes showed direct electrooxidation peak potential of sulfide at 381, 507, 400, and 850 mV vs. Ag/AgCl, respectively; however, the less positive oxidation potential and high catalytic current response of the ITO electrode made it the electrode of choice for the direct oxidation of sulfide. The effects of different electrolytes and buffer solutions on the CV responses were also evaluated. A linear concentration range up to 350 µM and a detection limit of 8.0 µM were achieved. CV response was highly reproducible, remaining unaffected even after 50 measurements. The sensor was found to have good selectivity, with no interference from sulfite, sulfate or chloride ions. The present findings demonstrate that the bare ITO electrode can be used as the basis of an inexpensive, sensitive, selective and robust sulfide sensor.